Sifting through science : teacher's guide - Lowell, Laura; Willard, Carolyn; GEMS (Project) (Berkeley, CA : Lawerence Hall of Science, University of California at Berkeley, 1997)
Presents three physical science activities about sinking and floating, magnetic and non-magnetic objects, and sifting and separating; and ends with an activity that combines the skills learned in the first three and teaches about recycling.
"Great explorations in math and science.".
"K-2 (can be adapted for prekindergarten).".
Includes bibliographical references.
Professional
Keywords: Science -- Study and teaching (Preschool); Science -- Study and teaching (Primary); Science -- Study and teaching